'It's in the air here': Atmosphere(s) of incarceration. Issue 3 (November 2022) - Turner, Jennifer; Moran, Dominique; Jewkes, Yvonne
Contrary to descriptions of a desensitising situation – with restrictions on movement, monotonous regimes and sparse surroundings – much research highlights imprisonment as sensorially and emotionally powerful. Following work within the 'turn to affect' that focuses on non-verbal, non-conscious and, often, non-human embodied experiences, scholars have attended to how such elements cohere into 'atmospheres'. Whilst the language of atmosphere is synonymous with the prison – a space that is widely anecdotally considered to conjure a particular 'feeling' – discussion of the mechanisms for and experiences of atmospheric production and consumption in this space has, thus far, evaded scholarly attention. Atmosphere is a word often used in prison literature, but it is rarely analytically unpacked. Accordingly, drawing on qualitative research data from individuals designing, and working and living in prisons, we focus on how various components – including aesthetics, olfaction, temperature, and the performances that arise from them – comprise sensory atmospheric affects in prison. In doing so, we find atmosphere(s) emerge – not simply from the materiality of the prison itself, but from cultural constructions of carceral and non-carceral landscapes and in conjunction with personal practice and preference. Accordingly, the prison is tied to particular constructions about what a prison should feel like and how people should (re)act to/in such spaces. In some cases, prison designers attempt to engineer particular atmospheres that cohere with wider political motivations around penal philosophies. However, despite the common reflection that prisons generate some kind of atmosphere, respondents are unable to offer a concrete description of what this may be, and much of our data highlights a definite precarity and changeability to atmospheric affect, which is likely to raise ambiguity around attempts to design carceral atmospheres.